Timeliness and completeness of medical records dispatched to medical record unit after patients discharge at Kampar hospital - Husin, Surayan Amir
Medical record management is among the most important operations in the hospital administrative functions. It is to ensure accessibility of the medical records, to create quality medical records, to encourage the greater utilization of hospital statistics as well as to participate in research and studies. The timeliness and completeness in the medical record management are essential for the prompt retrieval of the document for the readmission, for the continuing care of the patient when patient comes back for follow up and for the collection of health statistics for future planning of health services as well as to minimize the hospital liability against the legal action by hospital clients. Different country has different standard of timeliness and completeness of medical records. As for now, there are not many studies done on the timeliness aspect of medical record management locally or globally, which is supported by the research done by Lorence D, entitled, Measuring disparities in information capture timeliness across healthcare settings: effects on data quality. Kampar Hospital has been having difficulties in achieving the standard of patient care service indicator related to timeliness as well as problems related to the incomplete medical records. The objective of the study is to evaluate the timeliness and completeness of the medical record dispatched to Medical Record Unit after patient discharge. It aims in identifying the factors contributing to the delay in the timeliness in terms of processes, wards and staffs involved. It also looks into the completeness and accuracy of medical record documentation and the medical staff training background. An analysis on the medical record dispatch process shows that the completion of incomplete medical record particularly the discharge summary contributes to the delay in the process. It also reveals that Medical Officer is the most frequent position that contributes to the delay due to their involvement in the accomplishment of the discharge summary. A review conducted on 133 samples to determine the completeness and accuracy of the medical records, shows that less than half which is 43.6% of medical records in Kampar Hospital is complete with the presence of more than 90% critical elements and more than 80% non critical elements. It also shows almost the same findings in the percentage of fulfillment of medical record documentation as per requirement before dispatching the records to Medical Record Unit. The section in the medical record which is frequently incomplete and need improvement is identified as administrative section and clinical section. By identifying the locus of responsibility for each section, the hospital will be able to plan an appropriate intervention to improve the medical record documentation. The contributing factors identified as the sources of delays in the medical record dispatch process and the incompleteness of medical record documentation are inadequate policies related to medical record management, inadequate trainings, lack of experience and ignorance of the medical staffs on the importance of medical record management. This study will hopefully help the hospital to determine the appropriate actions for the improvement of the medical record management.
Management Study (MHA)--University of the Philippines Manila, 2011
Keywords: Medical Records